INCREASING INDUCTION MOTORS EFFICIENCY BY REDUCING ELECTROMAGNETIC LOADS - Olivian CHIVER (Carpathian Journal of Electrical Engineering, 2014)
The efficiency of any device is a major problem today. The design and construction of high efficiency motors is strongly required from the viewpoint of reducing energy consumption and protecting the environment. This paper deal with the problem of improving efficiency by reducing electrical and magnetic loads of these motors. Using the finite elements method (FEM), the authors will study the influence of these changes on the parameters and characteristics of the initial motor.